Formative online multiple-choice tests in nurse education: An integrative review. (January 2022) - Say, Richard; Visentin, Denis; Cummings, Elizabeth; Carr, Andrea; King, Carolyn
Abstract: Aim: The aim of this integrative review is to explore how formative online multiple-choice tests used in nurse education promote self-regulated learning and report on pedagogies that support their design. Background: Online multiple-choice tests are widely used as learning and formative assessment tools in a range of educational contexts. However, little is known about how these tools are used to promote patterns of learner self-regulation. It is important that nurses and nursing students develop the capability to self-regulate learning to be effective lifelong learners and navigate complex and unfamiliar practice environments. Design: A five-stage approach guided this integrative review: problem identification, literature search, data evaluation, data analysis and presentation. Method: A systematic search of ERIC, Web of Science, Ovid Medline, Scopus, PubMed, Embase and CINAHL was conducted in February 2021. Seventeen peer-reviewed papers were identified that discussed formative online multiple-choice tests in nurse education. Purposive sampling and ancestry searching identified an additional paper. Articles were analysed and sorted into themes of outcomes (presented as components of self-regulated learning theory) and pedagogy. Results: Formative online multiple-choice tests are used with good effect in nurse education as measured by knowledge gain and exam performance, increased confidence and learner satisfaction. There was no literature that explored metacognitive outcomes and minimal literature considered behavioural outcomes. Pedagogy supporting the implementation of multiple-choice tests was lacking in most articles. Conclusions: Formative online multiple-choice tests are widely used with good effect in nurse education. However, opportunities for further research on how these tools can encourage metacognition and self-regulatory behaviours is warranted.